Development And Validation Of Rp-Hplc Method For Simultaneous Estimation Of Rosuvastatin Calcium And Aspirin In Capsule Dosage Form - CHIRAGSINH SOLANKI,; NISHITKUMAR PATEL, (International Journal of Pharma and Bio Sciences, 2012)
A simple, specific, precise and accurate reversed-phase HPLC method was developed and validated for simultaneous estimation of rosuvastatin calcium and aspirin in capsule dosage forms. The separation was achieved by HyperChrom ODS-BP C18 column (200 mm x 4.6 mm, 5.0μm) using acetonitrile and 0.050 M potassium dihydrogen phosphate buffer adjusted to pH 3.0 with ortho phosphoric acid (55:45, v/v) as eluent, at a flow rate of 1 ml/min. Detection was carried out at wavelength 241 nm. The retention times of rosvastatin calcium and aspirin were 5.33 min and 3.56 min, respectively. The linearity was established over the concentration range of 0.5 - 6 µg/ml and 2.5 – 30 µg/ml with correlation coefficients (r 2) 0.9998 and 0.9995 for rosuvastatin calcium and aspirin, respectively. The mean recoveries were found to be in the range of 99.58% – 101.0% and 99.83%–100.11% for rosvastatin calcium and aspirin, respectively. The proposed method has been validated as per ICH guidelines and successfully applied to the estimation of rosuvastatin calcium and aspirin in their combined capsule dosage forms.